#### Answer

x = 0

#### Work Step by Step

-6(x - 3) - 26 = -8
Apply distributive property:
-6(x) - 6(-3) - 26 = -8
Simplify:
-6x + 18 - 26 = -8
-6x - 8 = -8
Add 8 to both sides:
-6x = 0
Divide both sides by -6:
x = 0

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

x = 0

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.